Controls on Methane Occurrences in Aquifers Overlying the Eagle Ford Shale Play, South Texas. Issue 4 (2nd March 2017) - Nicot, Jean‐Philippe; Larson, Toti; Darvari, Roxana; Mickler, Patrick; Uhlman, Kristine; Costley, Ruth
Abstract: Assessing natural vs. anthropogenic sources of methane in drinking water aquifers is a critical issue in areas of shale oil and gas production. The objective of this study was to determine controls on methane occurrences in aquifers in the Eagle Ford Shale play footprint. A total of 110 water wells were tested for dissolved light alkanes, isotopes of methane, and major ions, mostly in the eastern section of the play. Multiple aquifers were sampled with approximately 47 samples from the Carrizo‐Wilcox Aquifer (250‐1200 m depth range) and Queen City‐Sparta Aquifer (150‐900 m depth range) and 63 samples from other shallow aquifers but mostly from the Catahoula Formation (depth <150 m). Besides three shallow wells with unambiguously microbial methane, only deeper wells show significant dissolved methane (22 samples >1 mg/L, 10 samples >10 mg/L). No dissolved methane samples exhibit thermogenic characteristics that would link them unequivocally to oil and gas sourced from the Eagle Ford Shale. In particular, the well water samples contain very little or no ethane and propane (C1/C2+C3 molar ratio >453), unlike what would be expected in an oil province, but they also display relatively heavier δ 13 Cmethane (>−55‰) and δDmethane (>−180‰). Samples from the deeper Carrizo and Queen City aquifers are consistent with microbial methane sourced from syndepositional organic matter mixed with thermogenic methane input, most likely originating from deeper oil reservoirs and migrating through fault zones. Active oxidation of methane pushes δ 13 Cmethane and δDmethane toward heavier values, whereas the thermogenic gas component is enriched with methane owing to a long migration path resulting in a higher C1/C2+C3 ratio than in the local reservoirs. Abstract : Article impact statement : Dissolved CH4 in stacked aquifers over the Eagle Ford play is natural and mostly microbial.